2022
DOI: 10.1097/bot.0000000000002320
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Carbon Fiber Implants for Impending or Existing Pathologic Fractures

Abstract: Objectives:To evaluate the utility and complications of using carbon fiber implants (CFIs) compared with standard titanium alloy (TI) intramedullary implants for stabilization of impending or existing pathologic fractures.Design:Retrospective comparison.Patients/Participants:Ninety-four patients undergoing intramedullary fixation of 100 impending or existing pathologic fractures between 2014-2019 were identified for inclusion.Main Outcome Measurements:The primary outcome was postoperative complications. Other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…In the largest study of patients treated with CFRP nails to date, Piccioli et al found only 1 case of postoperative screw loosening in their cohort of 53 patients, with no evidence of hardware breakage 21 . Herzog et al, meanwhile, compared 53 cases of carbon fiber implants with 47 cases utilizing standard titanium 22 . In this study, they found 13% of patients had a complication related to implant failure, with 8 (15%) in the carbon fiber group and 5 (10%) in the titanium group.…”
Section: Carbon Implants For Treatment Of Extremity Tumorsmentioning
confidence: 99%
See 4 more Smart Citations
“…In the largest study of patients treated with CFRP nails to date, Piccioli et al found only 1 case of postoperative screw loosening in their cohort of 53 patients, with no evidence of hardware breakage 21 . Herzog et al, meanwhile, compared 53 cases of carbon fiber implants with 47 cases utilizing standard titanium 22 . In this study, they found 13% of patients had a complication related to implant failure, with 8 (15%) in the carbon fiber group and 5 (10%) in the titanium group.…”
Section: Carbon Implants For Treatment Of Extremity Tumorsmentioning
confidence: 99%
“…In the study by Herzog et al of 100 CFRP or titanium nails, 59 patients follow-up for more than 6 months, but 41 followed-up for less than 6 months. 22 Of these 41, 32 had died before 6-month follow-up and 9 were alive and doing well but unable to make appointments. Piccioli found a 15% rate of progression in their cohort with pathologic fractures, with 1 patient developing a stress fracture proximal to the distal static locking screw of their humeral nail, 1 month after surgery.…”
Section: Local Recurrence Disease Progression and Timingmentioning
confidence: 99%
See 3 more Smart Citations